Role of Hydration Status on the Pathogenesis and Management of Obesity - ALRosan, Sara H.; AL-Domi, Hayder A.; Alkhatatbeh, Mohammad J. (Jordan Journal of Agricultural Sciences, 2025)
Emerging evidence suggests a strong association between hydration status and the etiopathogenesis of obesity. This critical review highlights the possible role of hydration status in preventing, or at least ameliorating, the prevalence of obesity, a chronic, low-grade proinflammatory disease. PubMed, Google Scholar, ScienceDirect, and World Health Organization (WHO) databases were searched for literature published in English, using the following keywords search terms ‘water’, ‘water intake’, ‘hypohydration’ or ‘hydration’ and ‘energy intake’, ‘obesity’, ‘appetite’, ‘satiety’, ‘food consumption’, and ‘Body Mass Index (BMI)’ for the period between 2003 and 2023. The current review included data from clinical trials, cross-sectional stydies, cohort studies, published reviews, and case-control studies investigating the role of the hydration status in the development of obesity as well as prevention mechanisms. Rehydration by a moderate increase of daily water intake could be an effective, costless lifestyle modification for individuals at risk of developing obesity. Hypohydration could be one of the most important predisposing risk factors in both obesity pathogenesis and management, and its comorbidities via several mechanisms, mainly fat metabolism, thermogenesis, energy expenditure, food consumption, energy intake, hormonal balance, appetite regulation, and satiety regulation. Appropriate hydration status could help prevent or at least delay weight gain. Further clinical trials are required to verify the proposed mechanisms. The figure was created with BioRender.com.